DATA ACQUISITION AND INTERPRETATION BY USING GEOELECTRICAL RESISTIVITY METHOD FOR ASSESMENT OF LEACHATE MOVEMENT IN SARIMUKTI LANDFILL, WEST JAVA, INDONESIA - Yuneldi, Ari
Geophysical research is carried out to understand and analyze the subsurface structure of the earth which involves measuring physical parameters of rocks and other materials in the earth. Geoelectrical method learns about the nature of electricity in the earth by flowing DC electricity (Direct Current) into the ground. This research aimed to find out the location, accumulation, and spread of leachate contamination through resistivity values with Wenner array configuration. Data acquisition had been carried out in the around Sarimukti landfill area, Cipatat District, West Bandung Regency with total of ten (10) lines with electrode spacing ranged from 2.5 to 5 meter and length ranged between 80 and 160 meter by using multielectrode system. In this research, the geoelectric data processing was begun with processing field data by using a systematic calculation method with apparent resistivity equations to get pseudo resistivity values from each measurements of points.